Synthesis of Polymeric Nanoparticles for biomedical delivery applications - Crucho, Carina Isabel Correia (2016)
Polymeric nanoparticles (PNPs) have attracted considerable interest over the last few years due to their unique properties and behaviors provided by their small size. Such materials could be used in a wide range of applications such as diagnostics and drug delivery. Advantages of PNPs include controlled release, protection of drug molecules and its specific targeting, with concomitant increasing of the therapeutic index. In this work, novel sucrose and cholic acid based PNPs were prepared from different polymers, namely polyethylene glycol (PEG), poly(D,L-lactic-co-glycolic acid) (PLGA) and PLGA-co-PEG copolymer. In these PNP carriers, cholic acid will act as a drug incorporation site and the carbohydrate as targeting moiety. The uptake of nanoparticles into cells usually involves endocytotic processes, which depend primarily on their size and surface characteristics. These properties can be tuned by the nanoparticle preparation method. Therefore, the nanoprecipitation and the emulsion-solvent evaporation method were applied to prepare the PNPs. The influence of various parameters, such as concentration of the starting solution, evaporation method and solvent properties on the nanoparticle size, size distribution and morphology were studied. The PNPs were characterized by using atomic force microscopy (AFM), scanning electron microscopy (SEM) and dynamic light scattering (DLS) to assess their size distribution and morphology. The PNPs obtained by nanoprecipitation ranged in size between 90 nm and 130 nm with a very low polydispersity index (PDI < 0.3). On the other hand, the PNPs produced by the emulsion-solvent evaporation method revealed particle sizes around 300 nm with a high PDI value. More detailed information was found in AFM and SEM images, which demonstrated that all these PNPs were regularly spherical. ζ-potential measurements were satisfactory and evidenced the importance of sucrose moiety on the polymeric system, which was responsible for the obtained negative surface charge, providing colloidal stability. The results of this study show that sucrose and cholic acid based polymeric conjugates can be successfully used to prepare PNPs with tunable physicochemical characteristics. In addition, it provides novel information about the materials used and the methods applied. It is hoped that this work will be useful for the development of novel carbohydrate based nanoparticles for biomedical applications, specifically for targeted drug delivery.